A Review of The Strengths, Weaknesses, Opportunities, and Threats Facing Muslim-friendly Tourism in The Jepara District of Indonesia - Aan Zainul Anwar; Miftah Arifin; Elok Faiqotul Himma Noahdian; Sindy Aulia Octaviana (Idarotuna : Journal of Administrative Science, 2023)
This study aims to determine the strengths, weaknesses, opportunities, and threats to the potential of Jepara Regency as a Muslim-friendly tourism area. The benefits of this research can be used by the government in making policies regarding the development of Muslim-friendly tourism in Jepara. This research method is qualitative, and the data sources are interviews with the tourism office, tourism managers, and observations on tourist objects. Data analysis using SWOT The results of this study show that there is support, especially for the Jepara community, which is predominantly Muslim. Various types of natural tourism areas, religious tourism, and modern tourism have been supported by adequate and Muslim-friendly facilities. The weakness aspect is that there are still many access roads to tourist attractions that are inadequate, as well as religious facilities and toilets that are not clean. The opportunity to make Jepara a Muslim-friendly tourist area is the existence of social media support, which makes promotion easier and can reach all levels of society, while the threat is competitors from other cities who are also starting to integrate tourist attractions. Even so, Jepara is optimistic that it will remain the best Muslim-friendly tourism area.